2020
DOI: 10.3390/su12208587
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Development for Tourism Destination Business Environment and Competitive Advantages

Abstract: This study attempts to develop a measurement model of competitiveness utilized in the tourism sector, which appears to be fundamentally different in nature from traditional goods and services. Tourism destination competitiveness reflecting the generic characteristics should be considered diversified to notice the distinctive perspective between the business environment and competitive advantages. Criticism of some prior conventional literature stems from the lack of a rigorous process to find the structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…First, the major aspect of the present study centered on the cognitive process. Nevertheless, some recent studies asserted the emerging role of affect/emotion variables in tourists' post-purchase decision-making process and behaviors [49,50]. Therefore, it is also recommended for future research to consider the impact of affective/emotional process and cognitive factors for better explication of rural tourists' behaviors in Inner Mongolia.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…First, the major aspect of the present study centered on the cognitive process. Nevertheless, some recent studies asserted the emerging role of affect/emotion variables in tourists' post-purchase decision-making process and behaviors [49,50]. Therefore, it is also recommended for future research to consider the impact of affective/emotional process and cognitive factors for better explication of rural tourists' behaviors in Inner Mongolia.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Governança e competitividade de destinos turísticos: uma revisão de literatura em bases de periódicos nacionais e internacionais. Rosa dos 15(1),[180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198] http://dx.doi.org/10.18226/21789061v15i1p180 Sul, Chi & Han, 2020). Porém, na maioria das vezes os estudos tratam os constructos de maneira isolada, evidenciando que é preciso desenvolver estudos com relações teóricas e empíricas entre ambos os constructos.…”
Section: Metodologiaunclassified
“…The study found that China's urban business environment is affected by infrastructure, economic development, urban volume, and other factors, and there is an imbalance in regional development. Sul et al ( 2020 ) constructed the tourism competitiveness model of the business environment, clarified the important dimensions and competitive advantages of the business environment of tourism destinations, and provided an important theoretical basis for tourism management and decision-making. Dvorsky et al ( 2020 ) used the business environment data of 258 companies as a sample and found that the macroeconomic environment has a significant impact on the quality of the business environment, while the quality of the business environment in the service sector is not affected by monetary policy, corporate financing, and the consumer population.…”
Section: Literature Reviewmentioning
confidence: 99%